Come walk with me: Homelessness, nursing and engaged care. Issue 5 (October 2017) - Kelly, Linda; Luxford, Yoni
Abstract: To be without a home and live in public spaces or a rooming house is to experience chaos in one's daily life with compromised food, medication, income, and physical security. This, in turn, leads to a compromised ability to foster and maintain linkages with mainstream health services. Health outcomes for homeless individuals in Australia are shocking, or at least they should be. How do nurses work with people experiencing homelessness in Australia? What does person-centred care look like for a person who is homeless and for those who work with them? These are fundamental questions about nursing as skilful relational work in marginalised spaces with vulnerable people. Specialist nursing roles are relatively rare in these spaces. Creative non-fiction is a reflexive writing approach that portrays the complexity and humanity of persons who are key subjects in the narrative. A community health nurse uses it in an ordinary day at work as she engages with "Lisa", a young homeless woman, throughout a health intervention that doesn't end when she is admitted to hospital. The broader social aspects integral to working with this marginalised group are included to support the narrative. Suggestions are made regarding future research into this complex area of nursing practice and health care.